IMPLEMENTATION OF CROSS FUNCTIONAL TRAINING AT SEOUL CAFÉ TANJUNGPINANG - Evi Silvana Muchsinati; Shirley Shirley (ConCEPt - Conference on Community Engagement Project, 2022)
Seoul Café is one of the Micro, Small and Medium Enterprises (MSMEs) which is engaged in the culinary field by serving Korean specialties such as tteobokki, bibimbap, kimbap and other snacks that are produced by themselves to suit the taste of the Indonesian tongue. Seoul cafe is located on Jl. Soekarno Hatta, Tanjungpinang and has been operating for 2 years. However, since the COVID-19 pandemic, there has been an uncertain market demand for visitors to the Seoul Café, causing the human resources (HR) at the Seoul Café to be less organized, because as many as 40% of employees had to cut off employment due to the uncertainty of cafe visitors. The main goal that will be discussed in this practical work report is implementing cross functional training to increase the motivation for seoul café employees by creating a training module, the purpose of this training module is to improve workforce efficiency, performance quality, and better service to cafe customers and can be utilized as a learning knowledge, work attitudes in order to achieve certain work competencies. The module will be designed by using ADDIE model and will be handed over to related parties.